Optimalisasi Model Ipal SPALD-S dan Ipal SPALD-T (Studi Kasus Kelurahan Pajang, Kota Surakarta) - Emilia, Venesa Mega; Ilonka, Willy Anastasya (ENVIRO: Journal of Tropical Environmental Research, 2023)
Human needs for water and sanitation are intertwined, inadequate sanitation will adversely affect ecosystems and degrade water quality. Ecosystems must be preserved through effective sanitation management, as wastewater can damage ecosystems. Sanitation development is needed to manage wastewater before it is discharged into the environment/river. This research aims to determine which type of wastewater management such as septic tank, SPALD-S and SPALD-T is the best in terms of cost and quality with a case study in Kelurahan Pajang. The results of this study are expected to be useful for the community and government in determining the type of wastewater management that is environmentally friendly and efficient. It was found that the SPALD-T type is more cost-effective in terms of making and maintaining the type of wastewater network management, SPALD-T also has other advantages in terms of easier unit control and its construction is relatively safe from environmental pollution.